1999
DOI: 10.1046/j.1439-0272.1999.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human sperm-zona-free hamster oocyte binding and penetration by protein C inhibitor

Abstract: Protein C inhibitor is a heparin-dependent serine protease inhibitor present in plasma at about 0.08 mumol l-1. Protein C inhibitor inhibits activated protein C and other coagulation factors. Previously, we described the presence of high protein C inhibitor levels in human semen (3.1 mumol l-1) and showed potential roles of the inhibitor in human reproduction. Here, we show that protein C inhibitor is present in an active form in follicular fluid at about 0.1 mumol l-1 and that purified, functionally active hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…PAI-3 is a protease inhibitor that may be involved in human reproduction [31][32][33]. The precise role of this inhibitor in extracellular proteolysis has not been fully clarified, but it has been suggested that PAI-3 protects uPA from the inactivation by PAI-1 [34].…”
Section: Plasminogen Activator System In Endometriosismentioning
confidence: 99%
“…PAI-3 is a protease inhibitor that may be involved in human reproduction [31][32][33]. The precise role of this inhibitor in extracellular proteolysis has not been fully clarified, but it has been suggested that PAI-3 protects uPA from the inactivation by PAI-1 [34].…”
Section: Plasminogen Activator System In Endometriosismentioning
confidence: 99%
“…The concentration of PCI in follicular fluid is similar to that in plasma [1], [3]. In contrast, a 40-fold higher concentration (3–4 µM) is present in the seminal plasma [1].…”
Section: Introductionmentioning
confidence: 58%
“…Given that the physiological role of PSA is the degradation of the major proteins of seminal coagula, Semenogelin(Sg)-I and Sg-II, PCI also appears to be involved in the regulation of semen liquefaction [11]. In addition, seminal plasma PCI has been found to inhibit the binding and penetration of human sperm to zona-free hamster oocytes [3], [12]. The inhibitor thus appears to be necessary for several steps in fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Human seminal plasma contains very high concentrations of PCI, and it was shown that semen‐derived PCI interferes with binding and penetration of human sperm to zona‐free hamster oocytes . Altogether, PCI might influence several steps of reproduction.…”
Section: Proteins Of Interest In Pci−/− Mouse Testesmentioning
confidence: 99%